F. GONZÁLEZ DE CANALES (ed.) - Consideraciones sobre la obra de Rafael Moneo - de Teresa, Enrique (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
Francisco González de Canales (ed.) Consideraciones sobre la obra de Rafael Moneo Madrid: Arquia, La cimbra series n. 12, 2019, 241 pages. Softcover with flaps. Language: Spanish and Portuguese. 15 €. ISBN: 9788409036912